PEMANFAATAN NILAI-NILAI LUHUR WARISAN BUDAYA BANGSA DALAM PENDIDIKAN ANAK USIA DINI - Theresiana Ani Larasati (Widyariset, 2010)
This research aims to study the local wisdom in items of study of early childhood, knowing constraints, solutions,formulating the benefits, and provide suggestions for early childhood institutions (PAUD) that have not beenapplying local wisdom. The early childhood education institutions examined are two early childhood educationinstitutions in Semarang who have applied local wisdom in its lesson menu. Research design used was a qualitativedescriptive approach. Data obtained through interviews, supported by the observation, and literature. Results ofresearch shows that local wisdom on early childhood education conducted in the centers of art, nature centers,and material science, language centers, and sports centers. The application of local wisdom on early childhoodeducation is able to facilitate the growth of the confidence, pride, creativity, problem solving, and manners.